The allure of celebrities: unpacking their polysemic consumer appeal. (7th October 2019) - Wohlfeil, Markus; Patterson, Anthony; Gould, Stephen J.
Abstract : Purpose: This paper aims to explain a celebrity's deep resonance with consumers by unpacking the individual constituents of a celebrity's polysemic appeal. While celebrities are traditionally theorised as unidimensional semiotic receptacles of cultural meaning, the authors conceptualise them here instead as human beings/performers with a multi-constitutional, polysemic consumer appeal. Design/methodology/approach: Supporting evidence is drawn from autoethnographic data collected over a total period of 25 months and structured through a hermeneutic analysis. Findings: In rehumanising the celebrity, the study finds that each celebrity offers the individual consumer a unique and very personal parasocial appeal as the performer, the private person behind the public performer, the tangible manifestation of either through products and the social link to other consumers. The stronger these constituents, individually or symbiotically, appeal to the consumer's personal desires, the more s/he feels emotionally attached to this particular celebrity. Research limitations/implications: Although using autoethnography means that the breadth of collected data is limited, the depth of insight this approach garners sufficiently unpacks the polysemic appeal of celebrities to consumers. Practical implications: The findings encourage talent agents, publicists and marketing managers to reconsider underlying assumptions in their talent management and/or celebrity endorsement practices. Originality/value: While prior research on celebrity appeal has tended to enshrine celebrities in a "dehumanised" structuralist semiosis, which erases the very idea of individualised consumer meanings, this paper reveals the multi-constitutional polysemy of any particular celebrity's personal appeal as a performer and human being to any particular consumer.